Multicultural Sensitivity and Related Factors in Nursing Students of Zanjan University of Medical Sciences During the COVID-19 Pandemic - Zeynab Bakhteri; Nasrin Hanifi; Nasrin Jafari Varjoshani (Zanjan University of Medical Sciences and Health Services, 2022)
Background & Objective: Holistic care is provided by the ability to communicate effectively with patients from different cultures. In this respect, multicultural sensitivity helps communicate effectively with the patient. Therefore, the present study was conducted to investigate the multicultural sensitivity of nursing students and the factors affecting it during the COVID-19 pandemic. Materials & Methods: This cross-sectional correlation study was conducted on 245 nursing students of the Zanjan University of Medical Sciences in 2021. Data were collected using two questionnaires of demographic information and multicultural sensitivity. The multicultural questionnaire scored multicultural sensitivity on a Likert scale in the range of 1 to 5. Scores ≤ 3 were unfavorable multicultural sensitivities > 3 were desirable cultural sensitivities. Data analysis was performed using an independent t-test, analysis of variance, and logistic regression in the SPSS statistical software. Results: The mean total score of multicultural sensitivity was 3.64 ± 0.48. Also, the mean of multicultural sensitivity based on gender, residence, religion, bilingualism, semester, and field of study did not show a statistically significant difference (P < 0.05). The logistic regression model showed that gender and field of study could predict 3 to 6% of changes in multicultural sensitivity. Conclusion: The findings of this study showed that the multicultural sensitivity of students is favorable, despite their distance from the university environment. However, it is recommended to conduct training to make them more familiar with the cultural habits and health of Iranian ethnic groups.